THE IMPACT OF AL-ISLAM AND MUHAMMADIYAH LEARNING FRAMED BY RELIGIOUS MODERATION ON ADOLESCENT RESILIENCE - Hernawati Hernawati; Supala Supala (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aims to analyze the influence of Al-Islam and Muhammadiyahan (AIK) learning based on religious moderation on adolescent resilience in Muhammadiyah High School. This study uses a quantitative approach with an explanatory research design. The research sample consisted of 100 students in grades XI and XII who were selected through purposive sampling techniques. Data were collected using questionnaires that measured two main variables: AIK learning based on religious moderation and adolescent resilience. The results showed that AIK learning based on religious moderation had a positive and significant influence on adolescent resilience, with a regression coefficient value of 0.671 and significance (p) of 0.000. The AIK learning variable based on religious moderation was able to explain 39.1% of the variation in the level of student resilience. These findings confirm that AIK learning that prioritizes the values of religious moderation contributes to the formation of resilient and resilient adolescent characters in facing life's challenges. Therefore, strengthening AIK learning based on religious moderation is very important to be applied in education to support the formation of a young generation that is not only faithful, but also able to adapt to complex social and psychological dynamics